Hyperoxia does not affect oxygen delivery in healthy volunteers while causing a decrease in sublingual perfusion. (9th February 2018) - Smit, Bob; Smulders, Yvo M.; Eringa, Etto C.; Gelissen, Harry P. M. M.; Girbes, Armand R. J.; de Grooth, Harm‐Jan S.; Schotman, Hans H. M.; Scheffer, Peter G.; Oudemans‐van Straaten, Heleen M.; Spoelstra‐de Man, Angelique M. E.
Abstract: Objective: To determine the human dose‐response relationship between a stepwise increase in arterial oxygen tension and its associated changes in DO2 and sublingual microcirculatory perfusion. Methods: Fifteen healthy volunteers breathed increasing oxygen fractions for 10 minutes to reach arterial oxygen tensions of baseline (breathing air), 20, 40, 60 kPa, and max kPa (breathing oxygen). Systemic hemodynamics were measured continuously by the volume‐clamp method. At the end of each period, the sublingual microcirculation was assessed by SDF. Results: Systemic DO2 was unchanged throughout the study ( P slope = .8). PVD decreased in a sigmoidal fashion (max −15% while breathing oxygen, SD18, P slope = .001). CI decreased linearly (max −10%, SD10, P slope < .001) due to a reduction in HR (max −10%, SD7, P slope = .009). There were no changes in stroke volume or MAP. Most changes became apparent above an arterial oxygen tension of 20 kPa. Conclusions: In healthy volunteers, supraphysiological arterial oxygen tensions have no effect on systemic DO2 . Sublingual microcirculatory PVD decreased in a dose‐dependent fashion. All hemodynamic changes appear negligible up to an arterial oxygen tension of 20 kPa.